A tutela penal do crime de estupro e o princípio da proporcionalidade - Aoki, Luiz Gustavo de Oliveira Santos (2018)
This research aims to promote an analysis of the typical figures of rape crime and related to the basic principles of proportionality and reasonableness, which are elements that characterize the justice of the norm and vectors of interpretation of the criminal legal system. It begins with a study of the history of the typification of rape and other crimes against sexual dignity in Brazilian law. It follows with a verification of technical aspects of the current legislation that typifies rape and other crimes against sexual dignity. It promotes a general understanding of the general principles of criminal law and its vectors of interpretation, reasonableness and proportionality. In the final point, a general analysis is made of the relationship between the principle of reasonableness and the protection of the legal good of sexual dignity, as well as an incidental analysis of the principle of proportionality in relation to specific behaviors, namely lascivious kiss, touch of sexual connotation, libidinous act and rape of vulnerable, as well as the qualifiers of rape crimes, closing with a general study of proportionality in current legislative proposals. Bibliographic research and documentary research are adopted as technical procedures. As a method, the hypothetical-deductive is chosen to test the hypothesis, which is proven, that there is a disrespect rooted in the principle of reasonableness in the Brazilian legal discipline that protects sexual dignity, specifically in rape crimes, considering the possible repercussions of the typification format; and, in a latent way, a disregard for the principle of proportionality when the specific and correlated types are fixed for the crime of rape, which is noticeable in the incidental analysis of the principle of proportionality